Spontaneous perforated pyometra presenting as an acute abdomen: appraisal of three consecutive cases (Journal of Society of Surgeons of Nepal, 2018)
Introduction: Pyometra is the accumulation of purulent fluid in the uterine cavity caused by impaired drainage of pus due to benign or malignant conditions; rarely with resultant spontaneous uterine perforation brought about by uterine distension.Cases: We report three consecutive cases of spontaneous perforated pyometra in postmenopausal elderly women aged 60 to 70 years who presented with acute abdomen, initially diagnosed as hollow viscus perforation, demonstrated of having significant uterine perforation at laparotomy for which hysterectomy with bilateral salpingo-oophorectomy were done. Histopathological examination revealed features of necrosis of stroma with chronic endometritis without any evidence of malignancy in all the three cases.Conclusion: Spontaneous perforated pyometra, a grave complication necessitating prompt intervention, should always be kept as a possibility in all cases of suspected pyoperitoneum and acute abdomen in elderly postmenopausal women.